2007
DOI: 10.1539/joh.49.424
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Training Program on Reducing Needlestick Injuries/Sharp Object Injuries among Soon Graduate Vocational Nursing School Students in Southern Taiwan

Abstract: The Effectiveness of a Training Program on Reducing Needlestick Injuries/Sharp Object Injuries among Soon Graduate Vocational NursingSchool Students in Southern Taiwan: Ya-Hui YANG, et al. Institute of Occupational Safety and Health, Kaohsiung Medical University, Taiwan-Needlestick/ sharp injuries (NSIs/SIs) are a serious threat to medical/ nursing students in hospital internships. Education for preventing NSIs/SIs is important for healthcare workers but is rarely conducted and evaluated among vocational schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 21 publications
1
32
0
1
Order By: Relevance
“…• The frequency of the sharps injuries can substantially be reduced by target education to the technicians and the nurses [15,[17][18][19][20]]. …”
Section: Resultsmentioning
confidence: 99%
“…• The frequency of the sharps injuries can substantially be reduced by target education to the technicians and the nurses [15,[17][18][19][20]]. …”
Section: Resultsmentioning
confidence: 99%
“…Instructions about the transmission of blood borne diseases, standard safety measures, and expanding accessibility of insurance procedures must be provided. Yang et al (2007) specified that after instructive arbitration, the frequency of NSIs/SIs diminished altogether from 50.5% pre-test to 25.2% post-test, and the report rate expanded from 37.0% to 55.6%, separately. [13] Taking everything into account, this mediation essentially decreased the occurrence of NSIs/SIs and expanded the report rate of such incidences.…”
Section: Discussionmentioning
confidence: 99%
“…[13] More noteworthy is the susceptibility of nursing students, which may be due to lack of experience, inadequate ability and lack of proper information on how to handle certain instruments; nervousness; tiredness; absence of instructional exercises and trainings; carelessness lack of care for oneself and for others in the vicinity. [14] Therefore, the educators and managers in the nursing units are required to regularly evaluate the realities and practices in the clinical units. Having regular assessment and evaluation of the events and practices may not only help in the ramifications of the teaching approaches but may also instigate moral implications.…”
Section: Introductionmentioning
confidence: 99%
“…In a US hospital, the introduction in safety-engineered devices was also correlated with an overall decrease in percutaneous injuries 72) . Furthermore, in a recent Taiwanese study, educational intervention was shown to reduce the incidence of NSI and increase the reporting rate among student nurses 73) . Checklists to aid in the prevention of NSI are important and have already been trialled in Japan.…”
Section: Discussionmentioning
confidence: 99%